G174(P) A retrospective evaluation of non-acute child protection medicals performed in the last five years in a metropolitan borough in United Kingdom. (7th April 2014) - Wood, CM; Haywood, S; Green, P
Abstract : Aim: To identify differences in bruising distribution between disabled and non-disabled children, demographic variables associated with non accidental injury (NAI) Introduction: NAI is classified as: physical, emotional, neglect and sexual abuse. If NAI is suspected, a specialised medical can take place. Studies have shown that children with disabilities are more likely to be subjected to NAI than those children without, and present with different bruising patterns. There is no published data from a large group of children in the UK population. Method: Two hundred and forty three reports from 2008 to 2012 were included; the children were catagorised into four age groups based on the NSPCC Child abuse and Neglect Today document. The children's' demographic information, social circumstances, medical problems, injury type and bruising patterns were included. Results: Twenty eight percent of the 3–10 age group and 44% of 11–17 year olds had a disability. With significantly greater proportion of disabled children in the latter (P = 0.002). Within both groups 89% of the children with disabilities had communication/behavioural/speech problems. 183 of the children (75%) had bruises on examination. There was a significant proportional difference (P = 0.009) between the number of children with bruising to their thigh within the children with disabilities compared with the children without, in the group's 3–10 year olds (14/39 vs. 14/93) and 11–17 year olds (8/32 vs. 1/39). Ethnic minorities were over-represented (58.2%). Conclusion: This is the largest study of its kind in the UK. There was a significant difference between bruising distribution in children with disabilities and those without, however this was not related to physical disability. Children with disabilities are vulnerable to NAI and those with communication or behavioural problems appear to be at particular risk. Our study estimate exceeds NSPCC figures, where 15.1% of participating disabled children had communication/behavioural/speech problems. This suggests children with communication disabilities are of greater risk therefore education, social and healthcare workers need to be particularly vigilant whenever they come in contact with this group.